How spatial scale shapes the generation and management of multiple ecosystem services. Issue 4 (3rd April 2017) - Lindborg, Regina; Gordon, Line J.; Malinga, Rebecka; Bengtsson, Jan; Peterson, Garry; Bommarco, Riccardo; Deutsch, Lisa; Gren, Åsa; Rundlöf, Maj; Smith, Henrik G.
Abstract: The spatial extent of ecological processes has consequences for the generation of ecosystem services related to them. However, management often fails to consider issues of scale when targeting ecological processes underpinning ecosystem services generation. Here, we present a framework for conceptualizing how the amount and spatial scale (here discussed in terms of extent) of management interventions alter interactions among multiple ecosystem services. First, we identify four types of responses of ecosystem service generation: linear, exponential, saturating, and sigmoid, and how these are related to the amount of management intervention at a particular spatial scale. Second, using examples from multiple ecosystem services in agricultural landscapes, we examine how the shape of these relationships can vary with the spatial scale at which the management interventions are implemented. Third, we examine the resulting scale‐dependent consequences for trade‐offs and synergies between ecosystem services as a consequence of interventions. Finally, to inform guidelines for management of multiple ecosystem services in real landscapes, we end with a discussion linking the theoretical relationships with how landscape configurations and placement of interventions can alter the scale at which synergies and trade‐offs among services occur.